2021
DOI: 10.3390/children8060518
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of a 6-Year-Old Patient with Autism and Two Adjacent Duplications on 10q11.22q11.23. A Case Report

Abstract: Autism is a neurodevelopmental disorder presenting in the first 3 years of life. Deficits occur in the core areas of social communication and interaction and restricted, repetitive patterns of behavior, interests or activities. The causes of autism are unknown, but clinical genetic studies show strong evidence in favor of the involvement of genetic factors in etiology. Molecular genetic studies report some associations with candidate genes, and candidate regions have emerged from several genome-wide linkage st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Tritto et al reported a 6-year-old boy with 10q11.22q11.23 duplication presenting autism spectrum disorder, intellectual disability, developmental delay, hypotonia, gross-motor skills deficit, overgrowth and mild dysmorphic features. They proposed that 10q11.22q11.23 duplication was correlated with autism(29). According to the DECIPHER database and published literature, two morbid genes (WDFY4 and OGDHL) in this locus were closely associated with neurodevelopmental diseases.…”
mentioning
confidence: 99%
“…Tritto et al reported a 6-year-old boy with 10q11.22q11.23 duplication presenting autism spectrum disorder, intellectual disability, developmental delay, hypotonia, gross-motor skills deficit, overgrowth and mild dysmorphic features. They proposed that 10q11.22q11.23 duplication was correlated with autism(29). According to the DECIPHER database and published literature, two morbid genes (WDFY4 and OGDHL) in this locus were closely associated with neurodevelopmental diseases.…”
mentioning
confidence: 99%